Prevalencia y factores asociados con la filariosis por Mansonella ozzardi en 2 comunidades periurbanas de Iquitos, 2009 - Arróspide, Nancy (2015)
Introduction Three cases of M. ozzardi infection from 2 suburban communities in Iquitos, Peru, led to a suspicion of local transmission. The objective of the study was to determine the prevalence of filariasis by M. ozzardi and its associated factors among these communities. Materials and methods A cross-sectional study was performed, as well as an epidemiological survey and a thick smear blood test. Larvae and mosquitoes were collected. The adjusted OR (aOR) using multiple logistic regression was calculated. Results A total of 433 participants were enrolled; 58% were women. The prevalence of M. ozzardi was 1.4% and the associated factors included being a fisherman (aOR: 8.7; 95%CI: 1.1–76.0) and being on the Alto Nanay river (aOR: 11.2; 95%CI: 1.2–112.5). No significant evidence of simulidos or culicoides was found. Conclusion The low prevalence of M. ozzardi found suggests a foreign infection, probably derived from the Alto Nanay river.